Answer

Verified

382.8k+ views

**Hint:**In this problem, we have to solve the given differential equation and find the value of y. We can use the first order linear ordinary differential equation and we can derive an integrating factor and we can multiply the integrating factor to the differential equation. We can also solve this problem, by taking one term to the right-hand side and integrating on both sides and simply to solve for y.

**Complete step by step answer:**

We know that the given differential equation is,

\[y'+3y=0\]

We can write the term y’ as \[\dfrac{dy}{dx}\], we get

\[\dfrac{dy}{dx}+3y=0\]

Now we can add -3y on both sides, we get

\[\Rightarrow \dfrac{dy}{dx}=-3y\]

Now we can rearrange the above step by separating the variables, that is treating \[\dfrac{dy}{dx}\] as division and getting the y terms on one side and the x terms on the other side, we get

\[\Rightarrow \dfrac{dy}{y}=-3dx\]

We can now integrate on both the sides, we get

\[\begin{align}

& \Rightarrow \int{\dfrac{dy}{y}}=\int{-3dx} \\

& \Rightarrow \ln \left| y \right|=-3x+C\text{ }\because \int{\dfrac{1}{y}dy=\ln \left| y \right|},\int{\left( -3 \right)dx}=-3x \\

\end{align}\]

Now we can use the initial condition \[y\left( 0 \right)=4\], in the above step, we get

\[\begin{align}

& \Rightarrow \ln \left| 4 \right|=-3\left( 0 \right)+C \\

& \Rightarrow C=\ln \left| 4 \right| \\

\end{align}\]

We can substitute this C value, we get

\[\Rightarrow \ln \left| y \right|=-3x+\ln \left( 4 \right)\]

Now we can take exponent on both the sides, we get

\[\Rightarrow {{e}^{\ln \left| y\right|}}={{e}^{-3x+\ln \left| 4 \right|}}\]

Now we can use the exponent rule, we get

\[\begin{align}

& \Rightarrow y={{e}^{-3x}}.{{e}^{\ln \left| 4 \right|}} \\

& \Rightarrow y={{e}^{-3x}}.4\text{ }\,\,\, \because {{\text{e}}^{\ln \left| 4 \right|}}=4 \\

\end{align}\]

**Therefore, the value is \[y=4{{e}^{-3x}}\].**

**Note:**Students should know some basic integration formulas and rules to solve these types of problems. We should also know exponent rules to simplify this problem. We can also use the first order linear ordinary differential equation and we can derive an integrating factor and we can multiply the integrating factor to the differential equation to solve this problem.

Recently Updated Pages

How many sigma and pi bonds are present in HCequiv class 11 chemistry CBSE

Why Are Noble Gases NonReactive class 11 chemistry CBSE

Let X and Y be the sets of all positive divisors of class 11 maths CBSE

Let x and y be 2 real numbers which satisfy the equations class 11 maths CBSE

Let x 4log 2sqrt 9k 1 + 7 and y dfrac132log 2sqrt5 class 11 maths CBSE

Let x22ax+b20 and x22bx+a20 be two equations Then the class 11 maths CBSE

Trending doubts

Which are the Top 10 Largest Countries of the World?

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Difference Between Plant Cell and Animal Cell

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

Give 10 examples for herbs , shrubs , climbers , creepers

Select the word that is correctly spelled a Twelveth class 10 english CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE

Write a letter to the principal requesting him to grant class 10 english CBSE